Efforts to Increase Regional Retribution in Manokwari Regency 2016-2020: Analysis of Achievements and Constraints - Mansim, Naftali; Situmorang, Elina R; Tewernusa, Ketysia I (Side: Scientific Development Journal, 2025)
This research centers on the government's endeavors to enhance regional levy revenues, acknowledging the persistently minimal contribution of regional levies to the Original Regional Income. Data on Regional Retribution spanning from 2016 to 2020 was sourced from the Regional Asset and Financial Management Agency Report, while the analysis of government initiatives was conducted through extensive interviews with various sources. The study reveals that the government's endeavors to augment levy revenues remain notably deficient. These efforts primarily entail the enactment of regional regulations, yet they lack the provision of standard operating procedures and fail to implement rigorous monitoring of levy achievements. Consequently, the government's strategies for bolstering levy revenues are characterized by a considerable dearth of comprehensive frameworks and rigorous oversight mechanisms, underscoring the necessity for more robust and well- rounded approaches to address this fiscal challenge effectively.